Grenada : Third Review Under the Extended Credit Facility, Request for Modification of Performance Criteria, and Financing Assurances Review-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report ;, 2015)
This paper discusses Grenada's Third Review Under the Extended Credit Facility (ECF), Request for Modification of Performance Criteria (PCs), and Financing Assurances Review. Overall program implementation remains strong. All quantitative PCs for the third review were met. All structural benchmarks for the third review were implemented. The authorities advanced reforms to ensure the transparent and sustainable management of the Citizenship-By-Investment revenues, strengthen the fiscal policy framework, and improve public finance management. The IMF staff supports the completion of the third review under the ECF-arrangement, the modification of quantitative PCs, and completion of the financing assurances review.